The Value Implications, Practical Challenges, and Optimization Strategies for Early Childhood Educators Professional Development in the Context of Integrated Childcare and Education - Yang, Houqi (International Journal of Independent Research Studies, 2025)
This study examines the strategic significance and practical pathways for developing early childhood educators professional competencies in the context of integrated childcare and early education. The development of these educators professional capabilities holds multiple dimensions of value: For childrens early development, it serves as a foundational force for cognitive, emotional, social, and physical coordination development, while fostering secure attachment relationships and early learning environments. For improving the quality of childcare and early education, it ensures the coherence of educational philosophies, curriculum design, and teaching strategies, effectively implementing the "integration of care and education" principle during the 0-3 age stage. For teachers career development, it expands professional boundaries, cultivates "all-inclusive" early education teaching characteristics, and enhances career attractiveness and workforce stability. However, current practices face three major challenges: an incomplete professional competency indicator system with lack of targeted evaluation standards; fragmented pre-service training programs and overlapping curricula in teacher preparation, coupled with outdated and monotonous in-service training content; ambiguous regulations in policy documents regarding qualification certification, professional title evaluation, and compensation benefits, creating barriers between childcare institutions and kindergartens in terms of faculty, resources, and management. To address these issues, the study proposes a three-pronged optimization path of "standard development, training innovation, and institutional safeguards": establishing a three-dimensional competency framework encompassing "care skills + educational literacy + developmental support," and promoting higher education institutions to offer "integrated childcare and early education" teacher training programs.Specialized initiatives: Establish a three-tier training network integrating kindergartens, universities, and research institutions; develop modular, progressive courses; promote participatory training models; refine policies on qualification certification, professional advancement, and compensation incentives; deepen collaboration between childcare institutions and kindergartens; establish a professional development fund. This study provides theoretical support and practical pathways for teacher professional development in the context of integrated childcare and early education, demonstrating significant strategic value in enhancing early childhood development quality and promoting educational equity.